Feasibility and accuracy of UF/NCI phantoms and Monte Carlo retrospective dosimetry in children treated on National Wilms Tumor Study protocols. Issue 12 (12th August 2018) - Kalapurakal, John A.; Gopalakrishnan, Mahesh; Mille, Matthew; Helenowski, Irene; Peterson, Susan; Rigsby, Cynthia; Laurie, Fran; Jung, Jae Won; Fitzgerald, Thomas J.; Lee, Choonsik
Abstract: Purpose: This pilot study was done to determine the feasibility and accuracy of University of Florida/National Cancer Institute (UF/NCI) phantoms and Monte Carlo (MC) retrospective dosimetry and had two aims: (1) to determine the anatomic accuracy of UF/NCI phantoms by comparing 3D organ doses in National Wilms Tumor Study (NWTS) patient‐matched UF/NCI phantoms to organ doses in corresponding patient‐matched CT scans and (2) to compare infield and out‐of‐field organ dosimetry using two dosimetry methods—standard radiation therapy (RT) treatment planning systems (TPS) and MC dosimetry in these two anatomic models. Methods: Twenty NWTS patient‐matched Digital Imaging and Communications in Medicine (DICOM) files of UF/NCI phantoms and CT scans were imported into the Pinnacle RT TPS. The NWTS RT fields (whole abdomen, flank, whole lung, or a combination) and RT doses (10–45 Gy) were reconstructed in both models. Both TPS and MC dose calculations were performed. For aim 1, the mean doses to the heart, kidney, thyroid gland, testes, and ovaries using TPS and MC in both models were statistically compared. For aim 2, the TPS and MC dosimetry for these organs in both models were statistically compared. Results: For aim 1, there was no significant difference between phantom and CT scan dosimetry for any of the organs using either TPS or MC dosimetry. For aim 2, there was a significant difference between TPS and MC dosimetry for both CT scan and phantoms for all organs. Although the doses for infield organs were similar for both TPS and MC, the doses for near‐field and out‐of‐field organs were consistently higher for 90% to 100% of MC doses; however, the absolute dose difference was small (<1 Gy). Conclusions: This pilot study has demonstrated that the patient‐matched UF/NCI phantoms together with MC dosimetry is an accurate model for performing retrospective 3D dosimetry in large‐scale epidemiology studies such as the NWTS.